High-transmittance self-cleaning composite film based on PTFE film layer and manufacturing method thereof

The PTFE composite membrane prepared by multi-segment temperature-controlled casting process and plasma treatment solves the problems of poor light transmittance and insufficient interfacial bonding strength in the existing technology, realizes the continuous flat surface and excellent self-cleaning performance of the high-transmittance self-cleaning composite membrane, and extends the service life of the membrane material.

CN123025522APending Publication Date: 2026-11-03ACAD OF ENVIRONMENTAL PLANNING & DESIGN GRP CO LTD NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611476636.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing PTFE composite membranes have poor light transmittance, poor self-cleaning performance, and insufficient interfacial bonding strength in harsh environments such as sewage treatment plants, which makes the membrane material easily damaged in corrosive environments and results in high maintenance costs.

Method used

PTFE film layers are prepared using a multi-segment temperature-controlled casting process, and a fluorinated resin dispersion is coated on its surface to form an intermediate layer. The composite film is then formed by hot pressing with fiber fabric. Plasma treatment is used to improve the surface energy of PTFE and form a thickness-direction crystallinity gradient structure to enhance interfacial bonding.

Benefits of technology

A continuous and smooth functional surface was obtained, which improved light transmittance and self-cleaning performance, enhanced interfacial bonding strength, and significantly extended the service life of the membrane material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123025522A_ABST
    Figure CN123025522A_ABST
Patent Text Reader

Abstract

The application discloses a high-transmittance self-cleaning composite film based on a PTFE film layer and a manufacturing method thereof, and belongs to the technical field of film materials. The manufacturing method comprises the following steps: S1, preparing a PTFE film layer; S2, coating a fluorine-containing resin dispersion liquid on one side of the PTFE film layer, and performing heat treatment to form an intermediate layer, so that the PTFE film layer loaded with the intermediate layer is obtained; and S3, laying a fiber fabric on the intermediate layer, and performing hot pressing to embed the fiber fabric in the intermediate layer, so that a fiber reinforced layer is formed through cooling, and a composite film is obtained. The application has the advantages of a smooth surface, high light transmittance, high interfacial bonding strength and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of membrane material technology, and relates to a composite membrane, and more particularly to a high-transmittance self-cleaning composite membrane based on a PTFE outer layer and its manufacturing method. Background Technology

[0002] Polytetrafluoroethylene (PTFE) membrane materials have gained widespread attention and application in recent years in fields such as architectural membrane structures, sealed coverings for wastewater treatment plants, and photovoltaic greenhouses due to their excellent chemical corrosion resistance, weather resistance, and extremely low surface energy. In particular, PTFE membrane materials show promising application prospects in corrosive environments such as wastewater treatment plants due to their chemical inertness and hydrophobic properties.

[0003] In existing technologies, PTFE membrane materials for construction are mainly manufactured using a fiber fabric coating process. This process uses glass fiber fabric as the mechanical reinforcement substrate, and forms a composite membrane material by repeatedly impregnating and coating with PTFE dispersion, followed by high-temperature sintering and curing. However, this manufacturing process of weaving first and then coating has the following problems: the warp and weft weaving structure of the fiber fabric inevitably causes the coating surface to undulate with the fiber geometry, forming a micro-texture. In harsh environments such as sewage treatment plants, acidic droplets, dust particles, and microbial metabolites are easily embedded in the surface depressions, which seriously affect light transmittance and self-cleaning performance after long-term accumulation. Traditional coating processes rely on multiple immersion-sintering cycles to fill the fiber gaps, but during solvent evaporation and resin shrinkage, micron-sized pinholes are easily formed in local areas, providing a penetration path for corrosive media such as acidic droplets and VOCs gases, accelerating the chemical erosion and mechanical degradation of the fiber substrate. PTFE itself has extremely low surface energy and excellent chemical inertness, which means that the interfacial bonding between the coating and the glass fiber substrate mainly relies on mechanical interlocking and lacks effective chemical bonding. During long-term outdoor service, the risk of interlayer delamination increases significantly under the action of temperature difference, wind vibration, and rain and snow loads.

[0004] In addition, although conventional PVC and PVDF membranes are cheaper, they are far inferior to PTFE membranes in terms of chemical corrosion resistance, surface durability, and flame retardancy. Furthermore, plasticizer migration and surface stickiness of PVC membranes can exacerbate dirt adhesion during use, severely affecting light transmission and service life.

[0005] These problems are particularly prominent in specific operating conditions such as the enclosed space of wastewater treatment facilities and the corrosive environment of VOCs: acid mist corrosion leads to accelerated degradation of the membrane surface; organic pollutants continuously deposit on the membrane surface, resulting in a significant decrease in light transmittance; and maintenance operations in enclosed spaces are difficult and manual cleaning is costly. Therefore, developing new composite membrane materials with low maintenance costs and high long-term operational reliability is of significant practical importance. Summary of the Invention

[0006] This invention provides a high-transmittance self-cleaning composite membrane based on a PTFE outer layer and its manufacturing method, to overcome the problems of poor light transmittance, difficulty in cleaning, and poor strength of existing composite membranes.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for manufacturing a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer, comprising the following steps: S1: preparing a PTFE membrane layer; S2: coating one side of the PTFE membrane layer with a fluorinated resin dispersion, heat-treating to form an intermediate layer, thereby obtaining a PTFE membrane layer loaded with an intermediate layer; S3: laying a fiber fabric flat on the intermediate layer, hot-pressing to embed the fiber fabric into the intermediate layer, cooling to form a fiber reinforcement layer, thereby obtaining a composite membrane.

[0008] To optimize the above technical solution, the specific measures also include: Further, in step S1, the method for preparing the PTFE film layer includes the following steps: S11: maturing and preforming the PTFE dispersion to obtain a blank; S12: forming a film through a multi-stage temperature-controlled casting process to obtain a PTFE molten film; S13: cooling to obtain the PTFE film layer.

[0009] Further, the specific process of step S11 is as follows: the PTFE dispersion is placed in a sealed container and aged at 25~35℃ for 30~40 h, preferably at 30℃ for 36 h, to obtain a PTFE paste; the PTFE paste is compressed into a cylindrical blank in a preforming machine under a pressure of 3~8 MPa, preferably 5 MPa; the PTFE dispersion includes PTFE, lubricant, surfactant and dispersion medium; the lubricant is an isoparaffin; the surfactant is one or more of alkylphenol polyoxyethylene ether surfactants and perfluorooctanoic acid ammonium salt surfactants; the dispersion medium is deionized water; the mass ratio of PTFE, lubricant, surfactant and dispersion medium is 55~65∶1~5∶2~7∶30~40.

[0010] Further, in step S12, the multi-segment temperature-controlled casting process includes a dehydration section, an additive removal section, and a sintering section; the casting speed is 0.5~2 m / min, preferably 1 m / min; the temperature of the dehydration section is 100~150 ℃, preferably 120~140 ℃, the residence time is 3~10 min, preferably 5~8 min, and the atmosphere is air; the temperature of the additive removal section is 250~320 ℃, preferably 270~310 ℃, the heating slope is 5~10 ℃ / min, the residence time is 5~15 min, preferably 8~12 min, and the atmosphere is air; the temperature of the sintering section is 350~390 ℃, preferably 370~390 ℃, the residence time is 5~20 min, preferably 8~15 min, and the atmosphere is nitrogen.

[0011] Further, in step S13, the cooling process is as follows: both sides of the PTFE molten film are cooled simultaneously, with the cooling rate of the side carrying the intermediate layer being 2~8 ℃ / s and the cooling rate of the other side being 30~80 ℃ / s.

[0012] Specifically, the PTFE molten film is placed on one side of the intermediate layer on a temperature control plate, and a slower cooling rate is achieved by controlling the temperature of the temperature control plate; a cooling airflow is set on the other side, and a faster cooling rate is achieved by controlling the flow rate of the cooling airflow.

[0013] Furthermore, in step S2, the PTFE film layer is subjected to plasma treatment before coating the fluorinated resin dispersion.

[0014] Furthermore, in the plasma treatment, the plasma is argon plasma, the plasma treatment power is 300~500 W, preferably 350~450 W, and the treatment time is 10~120 s, preferably 30~90 s.

[0015] Further, in step S2, the fluorinated resin in the fluorinated resin dispersion is FEP or PFA, and the dispersion medium is water; the solid content of the fluorinated resin dispersion is 10-40%, preferably 20-30%; the coating is applied 1-5 times, preferably 2-4 times; drying is performed after coating and before heat treatment; the drying temperature is 80-150 ℃, preferably 100-130 ℃, and the drying time is 1-2 h; when the fluorinated resin is FEP, the heat treatment temperature is 290-300 ℃; when the fluorinated resin is PFA, the heat treatment temperature is 315-320 ℃; the heat treatment time is 0.5-1 h; and the thickness of the intermediate layer is 0.01-0.05 mm.

[0016] Further, the specific process of step S3 is as follows: the PTFE membrane layer loaded with the intermediate layer is placed with the intermediate layer facing upward; the fiber fabric is laid flat on the intermediate layer, and a protective film is covered under the PTFE membrane layer; then hot pressing is performed using an upper pressure plate and a lower pressure plate; finally, pressure is maintained and cooled to form a fiber reinforcement layer, and the protective film is peeled off to obtain the composite membrane.

[0017] Further, in step S3, the fiber fabric is a glass fiber fabric; the areal density of the fiber fabric is 100~500 g / m³. 2 300 g / m 2 The single filament diameter is 1~10 μm, preferably 5 μm; the protective film is a silicone rubber film or a polyimide film; the upper pressure plate is a heating pressure plate; when the fluorinated resin is FEP, the heating temperature of the upper pressure plate is 290~300 ℃; when the fluorinated resin is PFA, the heating temperature of the upper pressure plate is 315~320 ℃; the lower pressure plate is set as a supporting pressure plate; the hot pressing time is 60~300 s, preferably 120~240 s; the hot pressing pressure is 0.2~5 MPa, preferably 0.5~3 MPa.

[0018] Secondly, the present invention also provides a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer obtained by the above-described manufacturing method.

[0019] The beneficial effects of this invention are as follows: This invention effectively inhibits the transfer of fiber structure to the outer surface of PTFE, resulting in a continuous and smooth functional surface. Specifically, this invention constructs a PTFE functional outer layer with a thickness-direction crystallinity gradient structure. The highly crystalline regions inside provide rigid support for the outer layer. Under the melting flow and pressure of the FEP / PFA interlayer, the PTFE outer surface remains stable and does not undergo significant deformation. This effectively blocks the deformation transfer from the warp and weft undulations of the fiber fabric to the outer surface, thereby obtaining a continuous, dense, and smooth functional surface and reducing the physical adhesion of contaminants by microscopic depressions and gaps.

[0020] The composite film of this invention has high light transmittance and durable optical properties. Specifically, the low crystallinity region on the outer side of the PTFE film layer of this invention helps to reduce light scattering, and the smooth surface formed by the casting process gives the film material good light transmittance; moreover, due to the self-cleaning effect, the light transmittance decay rate can be lower than that of traditional film materials in long-term outdoor exposure and polluted environments.

[0021] The composite membrane of this invention exhibits excellent interfacial bonding strength. Specifically, the intermediate layer and fiber intercalation are prepared by coating. The semi-molten fluoropolymer resin can fully penetrate and fill the microscopic gaps in the fiber network, forming dense micron-level mechanical anchor points. The interfacial bonding strength is significantly improved compared to traditional impregnation coating and integral lamination processes.

[0022] The composite membrane of this invention possesses corrosion resistance and self-cleaning properties. Specifically, the multi-stage temperature-controlled casting process allows the melting, fusion, and densification of PTFE particles to be completed under controlled conditions. The dense PTFE continuous phase effectively blocks the permeation paths of acidic droplets and VOCs gases in corrosive environments such as wastewater treatment plants, protecting the internal fiber reinforcement layer from chemical erosion, thereby significantly extending the service life of the membrane material. Simultaneously, PTFE material itself has low surface energy. When used outdoors, rainwater is difficult to spread on the low surface energy PTFE membrane surface, instead rolling off in droplets. During this rolling process, it can carry away surface-deposited pollutants, achieving a self-cleaning effect based on rainwater rinsing, effectively reducing the frequency of manual cleaning and maintenance. Attached Figure Description

[0023] Figure 1 This is a schematic diagram of the hot pressing process of the composite film of the present invention; The labels in the attached diagram are: 1. PTFE membrane layer; 2. Intermediate layer; 3. Fiber reinforcement layer; A. Upper pressure plate; B. Lower pressure plate. Detailed Implementation

[0024] The specific embodiments of the present invention will be described below with reference to the accompanying drawings.

[0025] like Figure 1 As shown, the present invention provides a method for manufacturing a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer, comprising the following steps: S1: Preparation of PTFE membrane layer 1, specifically including the following steps: S11: The PTFE dispersion is matured and pre-formed to obtain a blank.

[0026] Specifically, the PTFE dispersion is placed in a sealed container and aged at 25-35 °C for 30-40 h, preferably at 30 °C for 36 h, to ensure that the lubricant is fully wetted and evenly distributed on the surface and between the PTFE powder particles, thereby improving the lubrication and molding properties of the PTFE powder and obtaining a PTFE paste. The PTFE paste is then compressed into a cylindrical blank in a preforming machine under a pressure of 3-8 MPa, preferably 5 MPa.

[0027] The PTFE dispersion comprises PTFE, a lubricant, a surfactant, and a dispersion medium. The lubricant is an isoparaffin. The surfactant is an alkylphenol polyoxyethylene ether surfactant. The dispersion medium is water. The mass ratio of PTFE, lubricant, surfactant, and dispersion medium is 55~65:1~5:2~7:30~40.

[0028] S12: PTFE molten film is obtained by multi-stage temperature-controlled casting process.

[0029] Specifically, the multi-stage temperature-controlled casting process includes a dehydration stage, an additive removal stage, and a sintering stage. The casting speed is 0.5~2 m / min, preferably 1 m / min. The temperature in the dehydration stage is 100~150 ℃, preferably 120~140 ℃, with a residence time of 3~10 min, preferably 5~8 min, and the atmosphere is air. The temperature in the additive removal stage is 250~320 ℃, preferably 270~310 ℃, with a heating rate of 5~10 ℃ / min, a residence time of 5~15 min, preferably 8~12 min, and the atmosphere is air, preferably with the volatiles discharged through a slight negative pressure of -10~-100 Pa, preferably -20~-60 Pa. The temperature in the sintering stage is 350~390 ℃, preferably 370~390 ℃, with a residence time of 5~20 min, preferably 8~15 min, and the atmosphere is nitrogen.

[0030] The dehydration section gently removes the dispersion medium and some low-boiling-point lubricants from the PTFE dispersion. If the temperature is too low, the dehydration rate is too slow, resulting in insufficient production efficiency and a risk of violent boiling during subsequent rapid heating, leading to bubble defects. If the temperature is too high, surface moisture evaporates too quickly, forming a hard shell that hinders the escape of internal moisture, causing residual moisture inside the membrane to bubble or create micropores in the subsequent high-temperature section. The additive removal section removes surfactants from the PTFE dispersion. Within this section, the surfactant undergoes thermal decomposition and molecularization, diffusing outwards from the membrane in gaseous form. By controlling the heating slope, the pyrolysis of the surfactant is completed before the PTFE particles begin significant melting and sintering, thus preventing the formation of closed micropores due to gas accumulation in the sintering section. In the sintering section, the crystalline regions on the surface of the primary PTFE particles fully melt, and the molecular chains undergo cross-particle entanglement through chain segment movement and diffusion, achieving full particle fusion and leveling. Meanwhile, the temperature of the sintering section is higher than the crystallization melting temperature of PTFE (approximately 327°C) but lower than the thermal decomposition initiation temperature of PTFE (above approximately 400°C), ensuring sufficient molecular chain movement while preventing thermal degradation. If the temperature is too low, the interparticle melting and fusion will be insufficient, leaving a large number of weak interfaces and microscopic voids in the membrane, significantly reducing mechanical and barrier properties. If the temperature is too high, PTFE may begin to undergo thermal decomposition, producing gaseous monomers such as tetrafluoroethylene (TFE) and hexafluoropropylene (HFP), forming bubbles and internal defects within the membrane, severely degrading its performance.

[0031] S13: Cooling to obtain PTFE membrane layer 1.

[0032] In a preferred embodiment, the cooling process is as follows: both sides of the PTFE molten film are cooled simultaneously and separately, with a cooling rate of 2~8 ℃ / s on one side and a cooling rate of 30~80 ℃ / s on the other side.

[0033] Specifically, one side of the PTFE molten film is placed on a temperature control plate, and a slower cooling rate is achieved by controlling the temperature of the plate. A cooling airflow is set on the other side, and a faster cooling rate is achieved by controlling the airflow rate.

[0034] By controlling the thermal difference along the thickness direction, different crystallization behaviors occur in different regions of the film, thereby achieving differentiated control of crystallinity in the thickness direction. Specifically, on one side, a slower cooling process promotes molecular chain rearrangement and crystal perfection, resulting in a higher crystallinity region on the inner side, improving the internal rigidity and dimensional stability of the film. On the other side, rapid cooling reduces molecular chain segment migration and crystal growth time, resulting in a lower crystallinity structure in this region, increasing the proportion of amorphous regions, thereby improving light transmittance and surface flexibility. By controlling the difference in cooling rates on both sides of the film, an asymmetric crystallization gradient PTFE film layer 1 is formed, characterized by low crystallinity, high amorphous phase ratio, high light transmittance, and high flexibility on one side, and high crystallinity, high rigidity, and high dimensional stability on the other side. This gradient structure can limit plastic deformation of the PTFE film layer 1 during subsequent hot pressing, providing a physical basis for its resistance to fiber transfer and maintenance of surface flatness.

[0035] S2: A fluorinated resin dispersion is coated on the side of the PTFE membrane layer 1 that is slowly cooled, and heat treatment is performed to form an intermediate layer 2, thus obtaining a PTFE membrane layer 1 loaded with an intermediate layer 2.

[0036] In a preferred embodiment, the PTFE membrane layer 1 is subjected to plasma treatment before coating with the fluorinated resin dispersion. During plasma treatment, the plasma is argon plasma, the plasma power is 300-500 W, preferably 350-450 W, and the treatment time is 10-120 s, preferably 30-90 s.

[0037] The PTFE film layer 1 is first subjected to plasma treatment, which uses high-energy particle bombardment to break some of the CF bonds on the PTFE surface and form active sites. After exposure to air, oxygen-containing polar functional groups are introduced to improve the surface energy and wettability of the PTFE, thereby promoting the uniform spreading and interfacial bonding of the fluorinated resin dispersion on the PTFE surface.

[0038] The fluorinated resin in the fluorinated resin dispersion is FEP or PFA, and the dispersion medium is water. The solid content of the fluorinated resin dispersion is 10-40%, preferably 20-30%. The coating is applied 1-5 times, preferably 2-4 times. Drying is performed after coating and before heat treatment. The drying temperature is 80-150℃, preferably 100-130℃, and the drying time is 1-2 h. When the fluorinated resin is FEP, the heat treatment temperature is 290-300℃; when the fluorinated resin is PFA, the heat treatment temperature is 315-320℃. The heat treatment time is 0.5-1 h. The thickness of the intermediate layer 2 is 0.01-0.05 mm.

[0039] FEP and PFA have similar perfluorocarbon chain structures to PTFE, exhibiting good interfacial compatibility. Furthermore, the melting temperature of FEP is approximately 260~280℃, and that of PFA is approximately 300~310℃, both lower than the melting temperature of PTFE (approximately 327℃). Therefore, an intermediate layer 2 with good continuity and fluidity can be formed through heat treatment without disturbing the main structure of the PTFE film layer 1.

[0040] By using an aqueous dispersion of fluorinated resin for in-situ coating, a tight bond can be achieved between the intermediate layer 2 and the PTFE membrane layer 1, avoiding the formation of microscopic air gaps at the interface. Specifically, the liquid dispersion, relying on surface tension and microscopic leveling properties, can fully wet the microscopic irregularities on the surface of the PTFE membrane layer 1, forming a molecular-level tight contact after drying. Simultaneously, the thickness can be precisely controlled by adjusting the concentration of the aqueous dispersion of fluorinated resin and the number of coating passes. The intermediate layer 2, with a thickness of 0.01~0.05 mm, provides sufficient resin melt to penetrate the fiber bundles while preventing disturbance to the PTFE membrane layer 1 caused by excessive lateral flow of resin overflow during hot pressing.

[0041] S3: Lay the fiber fabric flat on the intermediate layer 2, hot press to embed the fiber fabric into the intermediate layer 2, cool to form the fiber reinforcement layer 3, and obtain the composite film.

[0042] Specifically, the PTFE membrane layer 1, loaded with the intermediate layer 2, is placed with the intermediate layer 2 facing upwards. A fiber fabric is laid flat on the intermediate layer 2, and a protective film is placed under the PTFE membrane layer 1. Then, a hot-pressing process is performed using an upper pressure plate A and a lower pressure plate B. Finally, pressure is maintained and cooled to form the fiber reinforcement layer 3, and the protective film is peeled off to obtain the composite membrane.

[0043] The fiber fabric is a glass fiber fabric. The areal density of the fiber fabric is 100~500 g / m³. 2 300 g / m 2 The diameter of the single filament is 1~10 μm, preferably 5 μm. The protective film is a silicone rubber film or a polyimide film.

[0044] The upper pressure plate A is a heating plate that directly contacts the fiber and the intermediate layer 2. The heating temperature is set between the melting point of the intermediate layer 2 and the melting point of PTFE, providing heat to the intermediate layer 2 to melt it and soften it without affecting the rigid structure of the PTFE. When the fluoropolymer is FEP, the heating temperature of the upper pressure plate A is 290~300 ℃. When the fluoropolymer is PFA, the heating temperature of the upper pressure plate A is 315~320 ℃. The lower pressure plate B serves as a supporting plate, contacting the PTFE membrane layer 1, and is used to limit the transfer of heat to the outer surface of the PTFE membrane layer 1. The hot-pressing time is 60~300 s, preferably 120~240 s. The hot-pressing pressure is 0.2~5 MPa, preferably 0.5~3 MPa.

[0045] By hot pressing, semi-molten fluoropolymer resin can be forcibly extruded into the microscopic voids of the warp and weft interweaving of the fiber fabric, forming a microscopic mechanical interlocking structure. After cooling, the cured fluoropolymer resin forms a large number of micron-level anchor points in the fiber network, enabling the PTFE film layer 1 to achieve an interfacial bonding strength with the fibers that surpasses that of traditional coating and monolithic lamination processes.

[0046] The present invention also provides a high-transmittance self-cleaning composite membrane based on PTFE membrane layer 1, which is prepared by the above manufacturing method.

[0047] The present invention will be further described below with reference to specific embodiments.

[0048] Example 1 This embodiment provides a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer, the manufacturing method of which includes the following steps: S1: Mix PTFE, isoparaffin (Isopar G), alkylphenol polyoxyethylene ether surfactant, and deionized water, and cure in a sealed container at 30 °C for 36 h. Compress the cured PTFE paste into cylindrical blanks in a preforming machine under a pressure of 5 MPa.

[0049] The preformed blank is fed into a multi-stage temperature-controlled casting machine. The die gap is set to 0.5 mm, and the casting speed is 1 m / min. The three temperature zones are set as follows: Dehydration zone: temperature 120 ℃, residence time 5 min, atmosphere: clean air; Additive removal zone: temperature 270 ℃, residence time 8 min, heating slope 10 ℃ / min, atmosphere: clean air supplemented with a micro-negative pressure of -50 Pa to assist in the removal of volatiles; Sintering zone: temperature 370 ℃, residence time 15 min, atmosphere: high-purity nitrogen (purity ≥99.999%, oxygen content <5 ppm) to prevent high-temperature oxidation.

[0050] The PTFE molten film was cooled simultaneously from both sides. The cooling rate for the outer region was 60 °C / s, and the cooling rate for the inner region was 5 °C / s. The enthalpy of fusion ΔHm of the outer region was measured by DSC. 外 The enthalpy of melting (ΔHm) was 34 J / g, with a crystallinity of approximately 42%. The enthalpy of melting in the inner region of the membrane was measured by DSC. 内 The J / g concentration was 53, and the crystallinity was approximately 65%. The test results indicate that the PTFE film formed a crystallinity gradient structure through asymmetric cooling.

[0051] S2: After the PTFE film layer is cooled to room temperature, its inner surface is first treated with argon plasma at a power of 400 W for 60 s to improve the wettability and adhesion of the PTFE surface to the FEP dispersion. Subsequently, an FEP dispersion with a solid content of 20% is uniformly coated on the treated surface three times. After drying at 110 ℃ for 1 h, it is heat-treated at 290 ℃ for 1 h to form an intermediate layer with a thickness of approximately 0.02 mm.

[0052] S3: A surface density of 300 g / m² 2 A 5 μm diameter Class E glass fiber fabric is laid flat on top of the intermediate layer, and a silicone rubber film is then placed over the PTFE membrane layer for temporary protection before being fed into a hot press. The hot pressing parameters are: upper platen temperature 300 ℃, hot pressing pressure 1.2 MPa, and hot pressing time 120 s. During hot pressing, the FEP is in a semi-molten state, fully penetrating and filling the microscopic gaps within and between the glass fiber bundles. After hot pressing, pressure is maintained and cooling is performed to lower the composite membrane material temperature to room temperature. The silicone rubber film is then peeled off, revealing a smooth, defect-free surface on the PTFE membrane layer. The finished membrane material is obtained after trimming.

[0053] Example 2 This embodiment provides a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer, the manufacturing method of which includes the following steps: S1: Mix PTFE, isoparaffin (Isopar G), alkylphenol polyoxyethylene ether surfactant, and deionized water, and cure in a sealed container at 30 °C for 36 h. Compress the cured PTFE paste into cylindrical blanks in a preforming machine under a pressure of 5 MPa.

[0054] The preformed blank is fed into a multi-stage temperature-controlled casting machine. The die gap is set to 0.5 mm, and the casting speed is 1 m / min. The three temperature zones are set as follows: Dehydration zone: temperature 120 ℃, residence time 5 min, atmosphere: clean air; Additive removal zone: temperature 270 ℃, residence time 8 min, heating slope 10 ℃ / min, atmosphere: clean air supplemented with a micro-negative pressure of -40 Pa to assist in the removal of volatiles; Sintering zone: temperature 370 ℃, residence time 15 min, atmosphere: high-purity nitrogen (purity ≥99.999%, oxygen content <5 ppm) to prevent high-temperature oxidation.

[0055] The PTFE molten film was cooled simultaneously from both sides. The cooling rate was 40 °C / s for the outer region and 3 °C / s for the inner region. The enthalpy of fusion ΔHm for the outer region was measured by DSC. 外 The enthalpy of melting (ΔHm) was 40 J / g, with a crystallinity of approximately 49%. The inner region of the membrane was measured by DSC. 内 The concentration was 61 J / g, and the crystallinity was approximately 74%. The test results indicate that the PTFE film formed a crystallinity gradient structure through asymmetric cooling.

[0056] S2: After the PTFE film layer is cooled to room temperature, its inner surface is first treated with argon plasma at a power of 400 W for 60 s to improve the wettability and adhesion of the PTFE surface to the FEP dispersion. Then, a PFA dispersion with a solid content of 30% is uniformly coated on the treated surface four times. After drying at 130 ℃ for 2 h, it is heat-treated at 320 ℃ for 1 h to form an intermediate layer with a thickness of approximately 0.03 mm.

[0057] S3: A surface density of 300 g / m² 2 A 5 μm diameter Class E glass fiber fabric is laid flat on top of the intermediate layer, and a silicone rubber film is then placed over the PTFE membrane layer for temporary protection before being fed into a hot press. The hot pressing parameters are: upper platen temperature 320 ℃, hot pressing pressure 1.5 MPa, and hot pressing time 180 s. During the hot pressing process, the FEP is in a semi-molten state, fully penetrating and filling the microscopic gaps within and between the glass fiber bundles. After hot pressing, the pressure is maintained and cooled to lower the temperature of the composite membrane to room temperature. The silicone rubber film is then peeled off, revealing a smooth, defect-free surface on the PTFE membrane layer. After trimming, the finished membrane material is obtained.

[0058] Comparative Example This comparative example provides a composite membrane, the manufacturing method of which includes the following steps: Raw material preparation: Prepare three structural materials: PTFE membrane material, approximately 0.5mm thick; FEP film, 0.02mm thick, as the intermediate adhesive layer; and E-grade glass fiber plain weave fabric. Prepare the above three materials in roll form and install them onto the unwinding device of the double-belt press.

[0059] Multilayer lamination: PTFE membrane, FEP film, and E-grade glass fiber plain weave fabric are sequentially laminated in the order of PTFE membrane / FEP film / E-grade glass fiber plain weave fabric, with the FEP film sandwiched between the PTFE membrane and the E-grade glass fiber plain weave fabric, forming a three-layer laminated structure. The laminated material is continuously fed into a dual-belt press.

[0060] Heating and pressurizing composite: The composite material enters the heating and pressurizing zone of the double belt press, the heating temperature is set to 370 ℃, the pressure between the upper and lower steel belts is controlled at 1.2 MPa, and the residence time of the material in the heating zone is 120 s.

[0061] Pressure holding and cooling: After heating and pressurization are completed, the composite membrane immediately enters the cooling zone of the dual-belt press and is cooled by air at the same pressure as the heating zone until it is below 40°C to obtain the finished membrane material.

[0062] The performance of the membrane materials in each embodiment and comparative example was tested, and the results are shown in Table 1.

[0063] Table 1 Performance parameters of membrane materials in each embodiment and comparative example

[0064] The light transmittance test was conducted according to ISO 13468-1:1996. The test results show that, compared to the comparative example, the membrane material manufactured by the method of this invention has higher light transmittance and greater peel strength.

[0065] In this invention, unless otherwise stated, scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. Furthermore, the reagents, materials, and procedures used herein are all widely used in the relevant fields.

[0066] It should be noted that terms such as "upper" and "lower" used in the invention are merely for clarity of description and are not intended to limit the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the invention.

[0067] Finally, it should be noted that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for manufacturing a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer, characterized in that: Includes the following steps: S1: Preparation of PTFE membrane; S2: A fluorinated resin dispersion is coated on one side of the PTFE membrane layer, and heat treatment is performed to form an intermediate layer, thus obtaining a PTFE membrane layer loaded with an intermediate layer; the fluorinated resin in the fluorinated resin dispersion is FEP or PFA. S3: Lay the fiber fabric flat on the intermediate layer, hot press to embed the fiber fabric into the intermediate layer, cool to form a fiber reinforcement layer, and obtain a composite film.

2. The method for manufacturing a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer according to claim 1, characterized in that: In step S1, the method for preparing the PTFE membrane includes the following steps: S11: The PTFE dispersion is cured and pre-formed to obtain a blank; S12: PTFE molten film is obtained by multi-stage temperature-controlled casting process; S13: Cooling to obtain the PTFE membrane layer.

3. The method for manufacturing a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer according to claim 2, characterized in that: The specific process of step S11 is as follows: the PTFE dispersion is placed in a sealed container and aged at 25~35 ℃ for 30~40 h to obtain PTFE paste; the PTFE paste is compressed into a blank in a preforming machine under a pressure of 3~8 MPa. The PTFE dispersion comprises PTFE, a lubricant, a surfactant, and a dispersion medium; the lubricant is an isoparaffin; the surfactant is one or more of alkylphenol polyoxyethylene ether surfactants and perfluorooctanoic acid ammonium salt surfactants; the dispersion medium is deionized water; the mass ratio of PTFE, lubricant, surfactant, and dispersion medium is 55~65∶1~5∶2~7∶30~40.

4. The method for manufacturing a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer according to claim 2, characterized in that: In step S12, the multi-stage temperature-controlled casting process includes a dehydration stage, an additive removal stage, and a sintering stage; The casting speed is 0.5~2 m / min; The temperature of the dehydration section is 100~150 ℃, the residence time is 3~10 min, and the atmosphere is air; The temperature of the additive removal section is 250~320 ℃, the heating slope is 5~10 ℃ / min, the residence time is 5~15min, and the atmosphere is air; The temperature of the sintering section is 350~390 ℃, the residence time is 5~20 min, and the atmosphere is nitrogen.

5. The method for manufacturing a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer according to claim 2, characterized in that: In step S13, the cooling process is as follows: both sides of the PTFE molten film are cooled simultaneously and separately, with the cooling rate of the side carrying the intermediate layer being 2~8 ℃ / s and the cooling rate of the other side being 30~80 ℃ / s.

6. The method for manufacturing a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer according to claim 1, characterized in that: In step S2, the PTFE film layer is subjected to plasma treatment before coating the fluorinated resin dispersion. In the plasma treatment, the plasma is argon plasma, the plasma treatment power is 300~500 W, and the treatment time is 10~120 s.

7. The method for manufacturing a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer according to claim 1, characterized in that: In step S2, the solid content of the fluorinated resin dispersion is 10-40%; the coating is applied 1-5 times. Drying is performed after coating and before heat treatment; the drying temperature is 80~150 ℃ and the drying time is 1~2 h. When the fluorinated resin is FEP, the heat treatment temperature is 290~300 ℃; when the fluorinated resin is PFA, the heat treatment temperature is 315~320 ℃; and the heat treatment time is 0.5~1 h. The thickness of the intermediate layer is 0.01~0.05 mm.

8. The method for manufacturing a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer according to claim 7, characterized in that: The specific process of step S3 is as follows: the PTFE membrane layer loaded with the intermediate layer is placed with the intermediate layer facing upward; the fiber fabric is laid flat on the intermediate layer, and a protective film is covered under the PTFE membrane layer; then hot pressing is performed using an upper pressure plate and a lower pressure plate; finally, pressure is maintained and cooled to form a fiber reinforcement layer, and the protective film is peeled off to obtain the composite membrane.

9. The method for manufacturing a high-transmittance self-cleaning composite membrane based on a PTFE membrane layer according to claim 8, characterized in that: In step S3, the fiber fabric is a glass fiber fabric; the areal density of the fiber fabric is 100~500 g / m³. 2 The diameter of a single filament is 1~10 μm; The protective film is a silicone rubber film or a polyimide film; The upper pressure plate is a heating pressure plate; when the fluorinated resin is FEP, the heating temperature of the upper pressure plate is 290~300℃; when the fluorinated resin is PFA, the heating temperature of the upper pressure plate is 315~320℃; the lower pressure plate is configured as a supporting pressure plate. The hot pressing time is 60~300 s; the hot pressing pressure is 0.2~5 MPa.

10. A high-transmittance self-cleaning composite membrane based on a PTFE membrane layer, prepared by the manufacturing method according to any one of claims 1 to 9.